(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the causes behind the emergence of the jadid movement in Turkestan, its socio-historical foundations, and the stages of its development. It highlights that colonial policy, the crisis of traditional education, and the need for societal reform played a crucial role in shaping the movement. The educational and enlightenment activities of the jadids, the establishment of new-method schools, and the formation of national awakening ideas are analyzed. The article also describes the initial, developmental, and decline stages of the jadid movement based on scientific sources and reveals its significance in the socio-cultural life of Turkestan.